2008
DOI: 10.1021/jp8035814
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of Poly(acrylates) and Silver Nanoparticles: Structure and Applications for Antimicrobial Fabrics

Abstract: Silver−poly(acrylate) clusters have been synthesized in water by reduction of AgNO3 in the presence of poly(acrylates) of different molecular weights through two different methods, NaBH4 reduction and UV exposure. The structure of the clusters and the effect of the synthesis parameters on the size and polydispersity of the particles were evaluated by means of small-angle X-ray scattering (SAXS) and confirmed by UV−visible absorption and transmission electron microscopy (TEM). The results clearly show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 48 publications
0
70
0
Order By: Relevance
“…1a). The observation of absorption bands at this wavelength demonstrates the formation of spherical AgNPs [19,20,27]. Moreover, the absorption of the silver nanoparticles becomes stronger and sharper with increasing the silver concentration, which is indicative for the preparation of silver nanoparticles with narrower particles size distribution.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…1a). The observation of absorption bands at this wavelength demonstrates the formation of spherical AgNPs [19,20,27]. Moreover, the absorption of the silver nanoparticles becomes stronger and sharper with increasing the silver concentration, which is indicative for the preparation of silver nanoparticles with narrower particles size distribution.…”
Section: Resultsmentioning
confidence: 78%
“…There are studies in the literature concerning the antibacterial activity of AgNps stabilized by PVP against Escherichia coli and Staphylococcus aureus [14,18]. However, the antifungal effect of AgNps has received only scantly attention [19][20][21]. Therefore, an accent on the antifungal activity of AgNps/ PVP obtained by two different methods against different yeasts and molds, such as Candida albicans, Candida krusei, Candida tropicalis, Candida glabrata, and Aspergillus brasiliensis was made.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports stated that, the silver nanoparticles have potential antibacterial property against E. coli, S. aureus, Staphylococcus epidermis, Leuconostoc mesenteroides, Bacillus subtilis, Klebsiella mobilis and K. pneumonia (Benn and Westerhoff 2008;Chen and Chiang 2008;Falletta et al 2008;Hernandez-Sierra et al 2008;Ingle et al 2008;Jung et al 2009;Kim 2007;Kim et al 2007Kim et al , 2009Kvitek et al 2008;Raffi et al 2008;Ruparelia et al 2008;Smetana et al 2008;Sondi and Salopek-Sondi 2004;Vertelov et al 2008;Yang et al 2009;Yoon et al 2008a, b). It has been shown that silver nanoparticles prepared with a variety of synthetic methods have effective antimicrobial activity (Lok et al 2006;Baker et al 2005;Aymonier et al 2002;Melaiye et al 2005;Sondi and Salopek-Sondi 2004;Kim et al 2008;Lee et al 2008;Alt et al 2004).…”
Section: Proteus Morganii Staphylococcus Aureusmentioning
confidence: 98%
“…Silver nanoparticles (in situ synthesis by a chemical reduction method) Lactobacillus plantarum Electrospinning [82] Silver nanoparticles (in situ synthesis by a chemical reduction method) Lactobacillus plantarum Sol-gel dip-coating process [26] Silver-poly(acrylate) clusters Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, Candida albicans Immersion in the polyacrylate dispersions [83] Diamminesilver (I) silver [Ag(NH 3 ) 2 ] + Staphylococcus aureus and Escherichia coli Sol-gel dip-coating process [84] Silver nanoparticles (study as a function of the intensity and variation of the curing treatment)…”
Section: Antibacterial Agent Antibacterial Test Deposition Methodsmentioning
confidence: 99%
“…It is important to remark that this same methodology related to the in situ synthesis of AgNPs can be extrapolated to other different wet-chemistry techniques such as the sol-gel process, showing a complete inhibition of the bacteria growth [26]. Another approach based on the reduction of silver ions to silver nanoparticles is presented by Falleta et al [83] as a function of two different mechanisms such as the UV-radiation exposure and a Another approach based on the reduction of silver ions to silver nanoparticles is presented by Falleta et al [83] as a function of two different mechanisms such as the UV-radiation exposure and a synthetic chemical reduction process. In this work, the preparation of silver-polyacrylate clusters has been obtained and the resultant coloration depends on molecular weight of the protective agent as well as the mechanism of reduction to silver nanoparticles.…”
Section: Biocide Surface Treatmentsmentioning
confidence: 99%